Kv beta complex facilitates exercise-induced augmentation of myocardial perfusion and cardiac growth - Raph, Sean M.; Calderin, Ernesto Pena; Nong, Yibing; Brittian, Kenneth; Garrett, Lauren; Zhang, Deqing; Nystoriak, Matthew A. (Frontiers in Cardiovascular Medicine, 2024)
The oxygen sensitivity of voltage-gated potassium (Kv) channels regulates cardiovascular physiology. Members of the Kv1 family interact with intracellular Kvβ proteins, which exhibit aldoketo reductase (AKR) activity and confer redox sensitivity to Kv channel gating. The Kvβ proteins contribute to vasoregulation by controlling outward K + currents in smooth muscle upon changes in tissue oxygen consumption and demand. Considering exercise as a primary physiological stimulus of heightened oxygen demand, the current study tested the role of Kvβ proteins in exercise performance, exercise-induced adaptations in myocardial perfusion, and physiological cardiac growth. Our findings reveal that genetic ablation of Kvβ2 proteins diminishes baseline exercise capacity in mice and attenuates the enhancement in exercise performance observed after long-term training. Moreover, we demonstrate that Kvβ2 proteins are critical for exercisemediated enhancement in myocardial perfusion during cardiac stress as well as adaptive changes in cardiac structure. Our results underscore the importance of Kvβ proteins in metabolic vasoregulation, highlighting their role in modulating both exercise capacity and cardiovascular benefits associated with training. Furthermore, our study sheds light on a novel molecular target for enhancing exercise performance and improving the health benefits associated with exercise training in patients with limited capacity for physical activity.